Analisis Swot pada Usaha Mikro Kecil dan Menengah (UMKM) : (Studi Kasus pada Warung Bunda Dirga di Kecamatan Cikarang Utara) - Opi Yanti; Daspar Daspar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
One type of MSME that assists individuals in meeting their basic needs is the grocery store. The presence of small grocery stores greatly strengthens the local economy, especially in rural areas. Conventional grocery stores still survive and make a significant contribution to the local economy, despite the presence of several more contemporary retail companies in recent years. This study aims to evaluate the strategies used by MSME